Implementasi Media Augmented Reality terhadap Peningkatan Hasil Belajar IPAS di Sekolah Dasar: Literature Review - Tri Ulandari; Sigit Prasetyo (Lembaga Bale Literasi, 2026)
The background of this study is the growing need for innovative learning media in elementary schools to support students’ understanding of IPAS concepts in a more concrete and meaningful way in line with the advancement of educational technology. This study aims to systematically review the implementation of Augmented Reality (AR) in improving IPAS learning outcomes at the elementary school level through a Literature Review approach. The research method employed was a library research method by analyzing national and international journal articles, conference proceedings, academic books, and relevant research reports. The literature search was conducted through Google Scholar and several academic databases using the keywords “Augmented Reality,” “IPAS learning outcomes,” “IPAS learning,” and “elementary school.” Based on the inclusion criteria, 22 selected articles were analyzed using content analysis techniques. The findings indicate that the use of AR consistently has a positive impact on improving elementary school students’ IPAS learning outcomes, including cognitive aspects (conceptual understanding and material retention), affective aspects (learning motivation and interest), and psychomotor aspects (skills in manipulating and observing virtual objects). These results confirm that AR is an innovative learning medium that supports interactive and contextual learning aligned with the characteristics of 21st-century education. However, the effectiveness of AR implementation depends greatly on teachers’ readiness, the availability of facilities, and school infrastructure support. Therefore, systematic instructional planning, teacher training, and adequate technological resources are essential to optimize the use of AR in improving IPAS learning outcomes in elementary schools.